Ecosystem‐scale impacts of non‐timber forest product harvesting: effects on soil nutrients. Issue 5 (21st March 2017) - Ruwanza, Sheunesu; Shackleton, Charlie M.
Summary: The harvesting of non‐timber forest products (NTFPs) is a global phenomenon, the sustainability of which has been studied for many species at the individual and population level. However, the broader scale impacts of NTFP harvesting have been acknowledged but rarely examined. We assessed plant size and the soil attributes undercanopy and in the open, in replicate, paired harvested and non‐harvested sites for three NTFPs differing in the extent of biomass removed, i.e. timber for firewood from a tree ( Acacia karroo ), fruits from a cactus ( Opunita ficus‐indica ) and flowering culms from a grass ( Cymbopogon marginatus ). Soil variables tested included pH, resistivity, P, total N, nitrate nitrogen, ammonium nitrogen, K, Na, Ca and Mg. The extent of loss of soil nutrients decreased across the three NTFPs relative to the proportion of biomass removed. Thus, significant differences in more soil variables were evident for the firewood species, least for the fruit species and intermediate for the grass species. Lower soil pH, P, C and K were evident in soils collected underneath A. karroo, while losses in cations of Na, Ca and Mg were reported in soils underneath C. marginatus, and only NO3 N losses were recorded underneath O. ficus‐indica . Synthesis and applications . Our study reveals that while non‐timber forest product (NTFP) harvesting may affect soil nutrients, this is not uniform between species and is likely to be a function of the extent of biomass removed and harvesting frequency. This indicates the need for caution in generalisations about the ecosystem‐level impacts of NTFP harvesting as well as a concerted effort to better understand impacts at a greater range of scales than has been the case to date. Abstract : Our study reveals that while non‐timber forest product (NTFP) harvesting may affect soil nutrients, this is not uniform between species and is likely to be a function of the extent of biomass removed and harvesting frequency. This indicates the need for caution in generalisations about the ecosystem‐level impacts of NTFP harvesting as well as a concerted effort to better understand impacts at a greater range of scales than has been the case to date.